Depression increases the risk of inflammatory bowel disease, which may be mitigated by the use of antidepressants in the treatment of depression. Issue 9 (18th October 2018) - Frolkis, Alexandra D; Vallerand, Isabelle A; Shaheen, Abdel-Aziz; Lowerison, Mark W; Swain, Mark G; Barnabe, Cheryl; Patten, Scott B; Kaplan, Gilaad G
Abstract : Objective: Depression is associated with IBD, but the effect of antidepressants on IBD has been sparsely studied. We assessed the impact of depression and antidepressant therapies on the development of IBD. Design: The Health Improvement Network (THIN) was used to identify a cohort of patients with new-onset depression from 1986 to 2012. THIN patients who did not meet the defining criteria for depression were part of the referent group. The outcome was incident Crohn's disease (CD) or ulcerative colitis (UC). Cox proportional hazards modelling was performed to evaluate the rate of Crohn's disease or UC development among patients with an exposure of depression after controlling for age, sex, socioeconomic status, comorbid conditions, smoking, anxiety and antidepressant use including atypical antidepressants, mirtazapine, monoamine oxidase inhibitors (MAOI), serotonin norepinephrine reuptake inhibitors (SNRI), selective serotonin reuptake inhibitors (SSRI), serotonin modulators; and tricyclic antidepressants (TCA). Results: We identified 403 665 (7.05%) patients with incident depression. Individuals with depression had a significantly greater risk of developing CD (adjusted HR=2.11, 95% CI 1.65 to 2.70) and UC (adjusted HR=2.23, 95% CI 1.92 to 2.60) after controlling for demographic and clinical covariates. SSRI and TCA were protective against CD, whereas mirtazapine, SNRI, SSRI, serotonin modulators and TCA were protective for UC. Conclusion: Patients with a history of depression were more likely to be diagnosed with IBD. In contrast, antidepressant treatments were selectively protective for Crohn's disease and UC. These results may impact counselling and management of depression and IBD.